2009
DOI: 10.12693/aphyspola.116.1021
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Investigation of the Charge/Discharge Characteristics of Zinc/PVA-KOH/Carbon Cell

Abstract: Electrochemical properties of a zinc/polyvinyl alcohol-potassium hydroxide/carbon cell have been investigated. In this cell, PVA-KOH gel has been used as an electrolyte with PVA/KOH wt.% ratio of 60:40, while zinc and carbon rods served as electrodes. The cylindrical glass vessel of length 3.0 cm and of diameter 2.0 cm has been used as a cell compartment. The current-voltage characteristics and open circuit voltage-time, charge voltage/current-time and discharge voltage/current-time studies have been done. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Due to these advantages, it is being used in many electrochemical cells and sensors. [32,33] A similar kind of work was done by Saleem et al in which the electrochemical properties of Zn/ PVA-KOH-H 2 O-Iodine/C cell were studied for fixed concentration ratio of active materials. [32] These kinds of cells were found to be rechargeable and having good stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to these advantages, it is being used in many electrochemical cells and sensors. [32,33] A similar kind of work was done by Saleem et al in which the electrochemical properties of Zn/ PVA-KOH-H 2 O-Iodine/C cell were studied for fixed concentration ratio of active materials. [32] These kinds of cells were found to be rechargeable and having good stability.…”
Section: Introductionmentioning
confidence: 99%
“…[30] In last few years, organic semiconductor based electrochemical cells have been fabricated and investigated. [31][32][33][34] Among them, organic orange dye (OD) based electrochemical cells are more important [31,34] as they show good electrical conductivity in distilled water. [35] OD is stable at room temperature and has excellent solubility in H 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, polymer gel electrolyte with 60:40 ratio in zinc-carbon cell was examined by Saleem et al [30]. It was observed that the current charge/discharge efficiency was found to be 57 % [30].…”
Section: Research Articlementioning
confidence: 99%
“…Li rechargeable cells have received a tremendous attention for many years but their hazardous nature and the increasing cost have been well recognized now. As a result, attention of the scientific community has been focussed towards alternative anode materials such as Zn, Mg and Na (Sheha, 2013;Saleem, 2009). In this study, it was aimed to investigate the effect of the conductivity of the electrolyte on the performance of Zn rechargeable cells.…”
Section: Introductionmentioning
confidence: 99%